Uji Diagnostik Rasio Neutrofil-Limfosit Pada Apendisitis Akut Di Rumah Sakit Umum Zainoel Abidin Banda Aceh - Adyasa Manggala Putra, Idham; Syahputra, Dian Adi; Yusuf, Muhammad; Isa, Muntadhar Muhammad; Rahman, Safrizal; Ismy, Jufriady (Majalah Kedokteran Indonesia, 2021)
Introductions: Acute appendicitis is an inflammation that occurs in the Vermiformis appendix. Inflammatory response to acute appendicitis is characterized by the activation of cellular and molecular effectors, including recruitment and activation of neutrophils. The Neutrophil Lymphocytes Ratio (NLR) is a comparison of neutrophil counts with lymphocytes used as a simple benchmark. Methods: we analysed with observational diagnostic test analytical design of retrospective cross sectional studies. The study subjects were acute appendicitis patients at Zainoel Abidin General Hospital in 2018-2019. Subjects upon arrival performed a blood test, and then calculated NLR, the result of NLR count compared to post-appendectomy anatomical pathology examination. The data is analyzed with descriptive statistical analysis, ROC curve analysis and diagnostic tests.Results: There were 176 samples was came to emergency room with diagnosed appendicitis, the most age was 17-25 years (31.2%), 81 male (46%), 95 female (54%). From patological anatomy result were 129 acute appendicitis and 47 chronic appendicitis. From the AUC ROC 0.96 obtained cut off point NLR greater than 3,209 in acute appendicitis. Diagnostic tests obtained sensitivity 83,72% specificity 82,98%, positive guess value 97,71% and negative guess value 65,00% with 83,52% accuracy.Conclusion: we concluded NLR may predict diagnosis of acute appendicitis with NLR greater than 3,209, sensitivity scores of 83,72% specificity 82,98%.